A REVIEW OF FERTILISER TRIALS IN TUVALU AND KIRIBATI - K. TREWREN (International Coconut Community Journal, 1994)
A brief introduction is given to a programme of 34 fertiliser trials (possibly the largest programme of fertiliser trials in the world) that have been carried out in Tuvalu and Kiribati. Some of the more striking results that have emerged have been presented, and it is hoped that readers who would find more detailed information for use to them will ask for the relevant reports from the Department of Agriculture of the two countries concerned. The majority of the trials were conducted within the 1978 and 1993 period, being started by Trewren, and the longer running trials in Kiribati were continued by Edwards and, in most cases to their conclusion, by Barr. The results obtained have made it possible to formulate with some confidence recommendations on the manuring of coconuts on atolls, from seedlings in the nursery to mature palms in the field, including the rehabilitation of palms suffering from very severe deficiencies of trace elements and potassium. From foliar analysis, much useful information has been obtained on the inter‑relationships between nutrients, and in particular, on the fundamental importance of iron and other trace elements on the assimilation of macro‑nutrients and on the need to maintain a correct balance amongst trace elements. Further research is needed to identify a suitable source of nitrogen. Less important topics for research could be investigations into the optimum quantity of potassium chloride application to nursery seedlings and the optimum frequency of application of potassium chloride in the field.